Peran Guru Pendidikan Agama Islam Dalam Pembentukan Karakter Religius Pada Siswa Di SMAIT Al ‘Arabi - Hayati Najib Syam; Darwis Darwis; Ahmad Annuri (Turabian: Jurnal Pendidikan Islam, 2023)
Deviant behavior carried out by teenagers seems to be something we hear every day in the news and sometimes even happens around us. Religious character is formed through processes, one of these processes can be through education. One branch of the field of education is Islamic religious education. Islamic education is one aspect that can direct humans towards noble morals. So the skills and role of Islamic religious education teachers are very much needed in helping to shape the religious character of students. This research uses a qualitative approach and descriptive research type. Data collection methods use observation, interviews and documentation methods. Data analysis techniques use data reduction, data presentation, and drawing conclusions. Meanwhile, checking the validity of the data uses triangulation (source triangulation and technical triangulation). The results of the research show that the strategy for forming religious character is to start with the role of the Islamic religious education teacher himself and with the strategies and methods used so that the formation of religious character can be achieved. And the formation of the religious character of students at SMAIT Al-'Arabi has proven to be going well so that the habits that are carried out can enable students to do everything without coercion, as can be seen from the fact that students are consciously praying five times a day, reading the Koran before and after prayer, praying. dhuha, morning and evening dhikr and other habits. Although all parties must continue to synergize and cooperate between teachers, parents and students.